Acquired Platelet Dysfunction with Eosinophilia (APDE): Contemplating Physical Abuse - Anuar, Muhamad Azamin; A. Talib, Norlelawati; Misaridin, Nur Farah Izzati; Abu Bakar, Asrar; Mohamed, Mossad Abdelhak; Hasan , Taufiq Hidayat (IIUM Medical Journal Malaysia, 2020)
Introduction: APDE is an acquired, transient bleeding disorder characterised by normal platelet counts with eosinophilia. It was previously known as ‘nonthrombocytopenic purpura with eosinophilia’. We report a case of a 3-year-old boy with prolonged history of spontaneous unexplained bruising which was initially investigated by SCAN team for non-accidental injury (NAI). Case report: A 3-yearold boy attended clinic with a 4-month history of recurrent bruising. Parents were unsure of preceded illness, but he remained well with no history of trauma. He has unremarkable medical history and father is a thalassaemia carrier. Upon assessment in clinic, he was subsequently referred for suspected NAI and SCAN team led to a police report with a plan to review in 2-months. Parents later decided to bring the child for further medical assessments which revealed multiple bruises over both thighs, back of shoulder, loin and trunk with varying sizes and ages. They were all non-tender on palpation with no recognisable shapes or patterns. Blood results showed normal liver functions with slightly prolonged APTT 39.8 secs. He has normal platelet count with significant eosinophilia 2.2 x 10^9/L and occasional reactive lymphocytes. Reflecting this result, plan for platelet functions and von Willebrand tests were made. However, due to costs, we decided to treat the child with antihelminthic agent for possible parasitic infestation. He had 3 days course of albendazole and no further bruises appeared after 5 days of completing treatment. Discussion: The clinical presentation of APDE can mimic Idiopathic Thrombocytopenic Purpura in many ways yet normal platelet counts often leads to a delay in diagnosis. Reassuringly, the course of APDE is benign and no treatment is often required. Conclusion: Investigations however are costly, therefore treatment with anti-helminthic agent would be an alternative option in providing assurance to family and medical practitioners dealing with suspected cases.